2015
DOI: 10.1093/eurheartj/ehv548
|View full text |Cite
|
Sign up to set email alerts
|

Heart failure: when form fails to follow function

Abstract: Cardiac performance is normally determined by architectural, cellular, and molecular structures that determine the heart's form, and by physiological and biochemical mechanisms that regulate the function of these structures. Impaired adaptation of form to function in failing hearts contributes to two syndromes initially called systolic heart failure (SHF) and diastolic heart failure (DHF). In SHF, characterized by high end-diastolic volume (EDV), the left ventricle (LV) cannot eject a normal stroke volume (SV)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(77 citation statements)
references
References 50 publications
2
63
0
3
Order By: Relevance
“…The heart was able to eject a normal stroke volume but unable to accept a normal venous return, consistent with early concentric LV hypertrophy commonly seen in HF with preserved ejection fraction. This hypertrophic adaptation helps to maintain or enhance blood ejection but, at the same time, compromises chamber filling due to LV stiffness and, thereby, leads to a progressive deterioration of myocardial function until end-stage failure262728. The ballooned apex of the heart was reminiscent of broken heart syndrome or drug-induced Tako-tsubo cardiomyopathy1314.…”
Section: Discussionmentioning
confidence: 99%
“…The heart was able to eject a normal stroke volume but unable to accept a normal venous return, consistent with early concentric LV hypertrophy commonly seen in HF with preserved ejection fraction. This hypertrophic adaptation helps to maintain or enhance blood ejection but, at the same time, compromises chamber filling due to LV stiffness and, thereby, leads to a progressive deterioration of myocardial function until end-stage failure262728. The ballooned apex of the heart was reminiscent of broken heart syndrome or drug-induced Tako-tsubo cardiomyopathy1314.…”
Section: Discussionmentioning
confidence: 99%
“…This hypertrophy affects the LV in an asymmetrical way, mostly affecting the interventricular septum and leading to a redistribution of cardiac muscle, explaining the lack of effect on total cardiac mass. As reviewed by Katz and Rolett (2016), concentric hypertrophy and a decreased LV cavity volume are hallmarks of HFpEF. In this disease, further evolution of concentric hypertrophy may eventually contribute to the development of fibrosis, arrhythmias, progressive myocardial deterioration, and end-stage heart failure (Rockey et al 2015).…”
Section: Structural Changes Of the Aging Heart Ventricular Structurementioning
confidence: 99%
“…Experimental studies have suggested a potential role for cMyBP-C in diastolic function. For instance, the cMyBP-C null mouse model (116) and cMyBP-C homozygous and heterozygous knockin mouse exhibited diastolic dysfunction with elevated E/E' (120). Moreover, mutations in this protein were observed in patients with hypertrophic cardiomyopathy, among whom a significant percentage presented diastolic dysfunction, demonstrated by slowed cardiac relaxation (225).…”
Section: Altered Signaling Pathways In Hfpef As Potential Targets Formentioning
confidence: 99%